Political ideologies : an introduction / Andrew Heywood. - Heywood, Andrew (Red Globe Press, 2021)
The thoroughly updated 7th edition of this highly regarded text provides a clear, accessible introduction to the political creeds and doctrines that have dominated and shaped politics around the world.